Tafsir Ibn Abbas And The Role Of The Companions: Historical Criticism And Contemporary Implications - Suke Indah Khumaero; Muhammad Taufiq; Devi Aulia Utami; Nindira Mei Devita (Jurnal Ushuluddin, 2025)
This study examines how Abdullah ibn Abbas and other Companions contributed to the core principles of Qur'anic interpretation, focusing on their methods, characteristics, and relevance for today's challenges. Using a historical and qualitative approach, the research finds that the Companions' tafsir was a dynamic process that combined divine authority with contextual understanding and independent reasoning. Ibn Abbas relied on sources such as the Qur'an and Hadith with a focus on language and literature, while others, such as Ibn Mas'ud, took a more textual approach, and Ali ibn Abi Talib emphasised rational and ethical perspectives. The study also reviews criticisms about the chain of narration in the book Tanwīr al-Miqbās attributed to Ibn Abbas. In conclusion, the Companions' exegesis remains an important foundation but needs to be integrated with modern hermeneutical, thematic, and socio-cultural methods to address current issues. This approach turns the historical legacy into a dynamic source of inspiration for a more reflective and inclusive Islamic hermeneutics